Caracterização óptica, física e química de microesferas comerciais dos tipos IB e IIA para aplicação em demarcação horizontal. - (:unkn) unknown (Universidade Federal do Pampa, 2023)
Horizontal signage is very important for road safety once it allows a better view of the road in adverse traffic conditions. In order to have a better visibility of road signs, it is essential that the materials used for demarcation are retroreflective. Retroreflectivity occurs when glass microspheres are associated with paint in horizontal road signs. Within the types of microspheres, there are Type IB microspheres, which are applied to the paint before application on the road, and Type IIA, which are applied by spraying after application of the paint on the road. NBR 16184:2021 standard shows some parameters to standardize the production of microspheres, among than we can highlight: granulometric range, mass density, resistance to acid attack, presence of coating for adherence in acrylic resin, and the composition of the microspheres. On the other hand, NBR 14723: 2020 deals with retroreflectivity parameters of microspheres for 15-meter geometry. In this work, some analyzes proposed by NBR 16184:2021 and NBR 14723:2020 were replicated, in order to verify if these standards are being applied in two brands that produce glass microspheres. The results show that most of the parameters analyzed met the specifications of the standards, but some of them were not met by the companies.
Keywords: Engenharia civil; Rodovias - Sinalização; Microesferas; Demarcação horizontal; Civil engineering; Highways - signalling; Microspheres; Horizontal demarcation; CNPQ::ENGENHARIAS